Linearly Invariant Classes of Functions Analytical in the Half-Plane - Kirjackis, J.; Kiriyatzkii, E. G. (Nonlinear Analysis: Modelling and Control, 2004)
In present paper the properties of classes of introduced by authors functions analytical in the half-plane are investigated. These classes constructed by using special normalization of functions, automorphism of the half-plane and by operator actual on these classes. Such classes are called as linearly invariant ones. In case when domain is unit disc similar linearly invariant classes were considered by Ch. Pommerenke, V. Starkov, E.G. Kiriyatzkii.